High levels of ClNO2 enhance wintertime atmospheric oxidation capacity at a coastal site in North China - Weihang Sun; Xiaorui Chen; Yifan Jiang; Hengqing Shen; Zheng Zong; Likun Xue; Xinfeng Wang; Xiaohong Yao; Yating Gao; Tao Wang (Journal of Environmental Sciences, 2026)

Life-cycle monetization assessment for upgrading WWTPs to meet stricter discharge standards - Junran Liu; Yating Sun; Chencheng Dong; Xiaomeng Hu; Shauhrat S. Chopra; Hongtao Wang (Journal of Environmental Chemical Engineering, 2026)

Dual character of atmospheric NH3 on NH4NO3 aerosols — reducing evaporation indicated by perturbation analysis versus promoting formation predicted by thermodynamic modeling - Yinghua Lai; Qinchu Fan; Yating Gao; Lei Sun; Yang Gao; Huiwang Gao; Huaming Yu; Xiaohong Yao (Atmospheric Environment, 2026)

Cytotoxic aporphine alkaloids from the roots of Thalictrum baicalense Turcz. ex Regel. - Zhaojing Chen; Fangshen Liu; Lei Liu; Jinyuan Yang; Jingjing Xue; Hangao Yang; Dahong Li; Yating Sun; Huiming Hua (Phytochemistry, 2026)

Long-term exposure to air pollution, proteomic aging clocks, and liver-related outcomes in Chinese adults - Yating Huang; Dong Sun; Axing Lv; Jun Lv; Canqing Yu; Dianjianyi Sun; Pei Pei; Ling Yang; Yiping Chen; Huaidong Du; Dan Huang; Xiaoming Yang; et al. (Environmental Research, 2026)

Enantioselective migration, degradation, and metabolism of pyriproxyfen and its metabolites from tea garden to cup - Hongxia Li; Yue Hu; Yating Ning; Qing Zhong; Hezhi Sun; Xinru Wang; Mei Yang; Fengjian Luo; Li Zhou; Bingjun Han; Xinzhong Zhang (Food Chemistry, 2026)

Bismuth-induced exsolution in a durable and high-performance fuel electrode for reversible solid oxide cells - Ning Sun; Ting Chen; Hui Xu; Baoshui Wu; Yating Zhang; Xinyu Wang; Fangjun Jin; Kun Zheng; Lang Xu; Shaorong Wang (Chemical Engineering Journal, 2026)

Construction dual-temperature responsive hydrogel of hydroxypropyl methylcellulose and κ-carrageenan via formation of dynamic semi-interpenetrating physical structure - Mengya Sun; Qiongyu Wang; Jiulong An; Qiaolian Xu; He Li; Xinqi Liu; David Julian McClements; Yating Huang; Zhihua Pang (Carbohydrate Polymers, 2026)

The synergies and trade-offs of water-energy-carbon-land nexus in wastewater treatment plants - Junran Liu; Yating Sun; Sitian Jin; Ange Song; Jacek Makinia; Li Xie; Hongtao Wang (Journal of Water Process Engineering, 2026)

Microbial community composition and cooccurrence patterns driven by co-contamination of heavy metals and chlorinated hydrocarbons in groundwater - Yating Zhou; Ling Huang; Hang Wei; Mengqiang Sun; Qi Zou; Zhiliang Chen; Yutang Xiao (Journal of Hazardous Materials, 2026)

Towards sustainable municipal solid waste treatment: Life cycle environmental-economic analysis under waste sorting - Chenqi Gao; Rongxing Bian; Chengyue Yin; Xinran Du; Haoran Han; Yating Niu; Yingjie Sun; Yanan Wang (Journal of Environmental Sciences, 2026)

Study on the dissolution and recovery mechanism of bacterial cellulose by green ionic liquid designed based on COSMO-RS - Yue Lv; Wenqiang Jia; Hongda Cai; Leiying Ma; Yating Zhang; Mingdi Chen; Chaofan Sun; Xiuhua Zhao (Food Chemistry, 2026)

Correlation analysis of monosaccharide composition and in vitro antioxidant and hypoglycemic activities of Tremella fuciformis spore polysaccharides - Jianqiu Chen; Xiaoyu He; Shuting Zhou; Yujie Chen; Chunyuan Kong; Yating Deng; Shikai Ruan; Chengzhen Gu; Shujing Sun (Food Chemistry, 2026)

Design, synthesis, and mechanistic evaluation of alepterolic acid derivatives incorporating indole and piperazine moieties as anticancer agents targeting breast cancer - Lian Ma; Yanchun Sun; Binbin Zhang; Zixuan Tong; Yating Jia; Peixin Wang; Bingbing Ou; Jianguo Cao; Guozheng Huang (Molecular Diversity, 2025)

Colloidal properties of protein-stabilized emulsions in the presence of saliva: Impact on oral lubrication and sensory perception - Mengya Sun; Wenyan Tan; Yating Huang; David Julian McClements; Yongbao Wei; He Li; Zhihua Pang; Xinqi Liu (Food Research International, 2025)

Exploring the low‐carbon development model for a hazardous waste treatment park from a life cycle assessment perspective - Chenqi Gao; Yating Niu; Xinran Du; Runze Zhu; Rongxing Bian; Ya'nan Wang; Yingjie Sun; Weihua Li; Qingjian Zhang; Huilai Chen (Journal of Industrial Ecology, 2025)
China is actively committed to mitigating carbon emissions through its “Dual Carbon” and “Zero‐Waste Cities” strategies. Hazardous waste (HW) treatment, a significant source of greenhouse gas (GHG) emissions, plays a crucial role in achieving carbon reduction targets. This study systematically assessed the carbon emissions and low‐carbon pathways of a representative multi‐HW treatment park in Qingdao using life cycle assessment and life cycle cost methodologies. In 2020, the total net GHG emissions of the HW park were 49,669.3 t CO 2 ‐eq, with an average emission intensity of 1181.1 kg CO 2 ‐eq per tonne of HW. Among the various treatment systems, medical waste (MW) incineration exhibited the highest GHG emission intensity (1377.6 kg CO 2 ‐eq/t MW), followed by industrial hazardous waste (IHW) incineration (1076.4 kg CO 2 ‐eq/t IHW), fly ash/slag treatment (9.7 kg CO 2 ‐eq/t HW), and physicochemical treatment (8.5 kg CO 2 ‐eq/t HW). Three integrated low‐carbon pathways demonstrated that utilizing waste heat for heating exhibited the highest carbon mitigation potential, achieving up to −403.6 kg CO 2 ‐eq/t IHW, followed by technological improvement and resource recycling. The combined low‐carbon scenario could achieve a 49.5% reduction in total carbon emissions compared to the baseline scenario. Furthermore, economic performance improved, with treatment benefits increasing from 3431.3 RMB/t IHW to 3948.5 RMB/t IHW due to enhanced energy efficiency and resource recovery. This study provides a framework for assessing multi‐HW parks’ carbon footprints and offers strategic insights for low‐carbon, resource‐efficient waste management. The findings also support sustainable multi‐HW management and contribute to climate and decarbonization efforts.

Genomic and phenotypic analysis of virulence, antimicrobial resistance, and transmission routes of Vibrio vulnificus from food and clinical sources in China - Yating Xu; Ruanyang Sun; Zhiwei Zheng; Lianwei Ye; Mingxiu Peng; Sheng Chen (Food Research International, 2025)

Targeted capture of Bacillus thuringiensis using phage endolysin cell wall binding domain with high recognition specificity - Qin Peng; Lushuang Wang; Gege Feng; Xi Chen; Dan Li; Yating Zeng; Yingqi Qian; Zhirou Sun; Yihui Yuan (Chemical Engineering Journal, 2025)

New insights into the effect of H2S stress on CH4 oxidation in landfill cover soils from the CH4-derived carbon allocation and its microbial mechanism - Rongxing Bian; Yating Niu; Xinran Du; Chenqi Gao; Tingxue Zhang; Runze Zhu; Yingjie Sun; Yanan Wang (Process Safety and Environmental Protection, 2025)

Comparative evaluation of maize chromosome pretreatment using cold water and 8-hydroxyquinoline - Lulu Hou; Yating Su; Shixin Li; Haidong Yu; Yuhui Sun (Planta, 2025)

Unleashing potent antimicrobial synergy: Carnosic acid and caffeic acid tackle multidrug-resistant MRSA - Rulin Jin; Yating Wang; Weiqing Lan; Yong Zhao; Xiaohong Sun (Food Bioscience, 2025)

Fullerenols hijack lysosomes to disrupt inter-organellar crosstalk and block autophagy pre-activated by mTOR inhibitors for cancer cell PANoptosis - Hedong Qi; Xue Li; Jing Ma; Jiacheng Sun; Yating Liu; Xin Wang; Kelong Fan; Chunying Shu; Chunru Wang (Science Bulletin, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Effect of cadmium and fumonisin B1 co-exposure on mitochondrial dysfunction and ferroptosis pathway in Caenorhabditis elegans - Yating Wang; Yongli Ye; Jian Ji; Jia-Sheng Wang; Lili Tang; Lanlan Zhang; Yufeng Li; Jiadi Sun; Lina Sheng; Xiulan Sun (Journal of Hazardous Materials, 2025)

Innovative microbial activators for enhanced bioremediation of oil-contaminated soils: mechanistic insights - Yating Deng; Wujuan Sun; Yongbin Li; Jun Wei; Ruirui Rao; Qiongyu Cao; Sichang Wang; Qunzheng Zhang; Congyu Ke (World Journal of Microbiology and Biotechnology, 2025)

Analysis of carbon reduction potential from typical municipal solid waste incineration plants under MSW classification - Chenqi Gao; Rongxing Bian; Ping Li; Chengyue Yin; Xiao Teng; Jinran Zhang; Shudan Gao; Yating Niu; Yingjie Sun; Yanan Wang; Huawei Wang (Journal of Environmental Management, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Organic fertilizer significantly mitigates N2O emissions while increase contributed of comammox Nitrospira in paddy soils - Han Sun; Youfa Li; Yating Xing; Dylan Bodington; Xing Huang; Chenxiao Ding; Tida Ge; Hongjie Di; Jianming Xu; Cécile Gubry-Rangin; Yong Li (Science of The Total Environment, 2024)

Nature-inspired ultrathin wood-based interfacial solar steam generators for high-efficiency water purification - Min Li; Yating Sun; Yuzhang Lei; Gonggang Liu; Heng Jiang; Yong Wang; Shanshan Chang; Xianjun Li; Jinbo Hu (Desalination, 2024)

Multi-level pumping water system from bioengineering wood microstructure by self-growing mycelium for boosting photothermal evaporation efficiency - Yuzhang Lei; Yating Sun; Yanda Li; Kai Han; Gonggang Liu; Shanshan Chang; Yuan Zhu; Xianjun Li; Yue Liu; Jinbo Hu (Chemical Engineering Journal, 2024)

Green and sustainable extraction of phycocyanin from Spirulina platensis by temperature-sensitive polymer-based aqueous two-phase system and mechanism study - Di Hu; Ruru Xu; Yating Jin; Shuqing Sun; Jing Ye; Jiajia Wu; Zhiyuan Dai; Jia-Wei Shen; Yanbin Lu (Bioresource Technology, 2024)

Multi-omics association study of hexadecane degradation in haloarchaeal strain Halogranum rubrum RO2-11 - HeLang Huang; CaiYun Xie; ZiYuan Xia; ZhaoYong Sun; YaTing Chen; Min Gou; YueQin Tang; HengLin Cui; XiaoLei Wu (Environmental Research, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Fusion of Multi-Layer Attention Mechanisms and CNN-LSTM for Fault Prediction in Marine Diesel Engines - Jiawen Sun; Hongxiang Ren; Yating Duan; Xiao Yang; Delong Wang; Haina Tang (Journal of Marine Science and Engineering, 2024)
Timely and effective maintenance is imperative to minimize operational disruptions and ensure the reliability of marine vessels. However, given the low early warning rates and poor adaptability under complex conditions of previous data-driven fault prediction methods, this paper presents a hybrid deep learning model based on multi-layer attention mechanisms for predicting faults in a marine diesel engine. Specifically, this hybrid model first introduces a Convolutional Neural Network (CNN) and self-attention to extract local features from multi-feature input sequences. Then, we utilize Long Short-Term Memory (LSTM) and multi-head attention to capture global correlations across time steps. Finally, the hybrid deep learning model is integrated with the Exponential Weighted Moving Average (EWMA) to monitor the operational status and predict potential faults in the marine diesel engine. We conducted extensive evaluations using real datasets under three operating conditions. The experimental results indicate that the proposed method outperforms the current state-of-the-art methods. Moreover, ablation studies and visualizations highlight the importance of fusing multi-layer attention, and the results under various operating conditions and application scenarios demonstrate that this method possesses predictive accuracy and broad applicability. Hence, this approach can provide decision support for condition monitoring and predictive maintenance of marine mechanical systems.

Epidemiological and genetic characterization of multidrug-resistant non-O1 and non-O139 Vibrio cholerae from food in southern China - Yating Xu; Zhiwei Zheng; Ruanyang Sun; Lianwei Ye; Edward Wai-Chi Chan; Sheng Chen (International Journal of Food Microbiology, 2024)

Heavy metal pollution status, children health risk assessment and source apportionment in farmland soils in a typical polluted area, Northwest China - Shun Chen; Yating Gao; Chengkui Wang; Huilin Gu; Mingkun Sun; Yuhui Dang; Shiwei Ai (Stochastic Environmental Research and Risk Assessment, 2024)

Simultaneous removal of As(V) and sulfamethazine from water in FeS2-H2O2 system - Wen Li; Shanshan Yang; Shuiyu Sun; Tianming Wang; Qi Yao; Jingyi Zhan; Shanwen Ye; Yating Liang; Yunzhuo Deng; Wenxiang Wang; Hongsheng Fang; Yunmei Cai (Chemical Engineering Journal, 2024)

The association between blue light exposure and incidence of type 2 diabetes: A prospective study of UK biobank - Cheng Wang; Yang Zhao; Qianqi Hong; Yating Lei; Shengyuan Wang; Weiqi Wang; Wei Wei; Changhao Sun; Tianshu Han (Environmental Research, 2024)

Trim and Engine Power Joint Optimization of a Ship Based on Minimum Energy Consumption over a Whole Voyage - Yanyun Yu; Hongshuo Zhang; Zongbao Mu; Yating Li; Yutong Sun; Jia Liu (Journal of Marine Science and Engineering, 2024)
Trim optimization is an available approach for the energy saving and emission reduction of a ship. As a ship sails on the water, the draft and trim undergo constant changes due to the consumption of fuel oil and other consumables. As a result, the selection of the initial trim is important if ballasting or shifting liquid among the tanks is not considered during a voyage. According to the characteristics of ship navigation and maneuvering, a practical trim optimization method is proposed to identify the Optimal Trim over a Whole Voyage (OTWV) which makes the fuel consumption of the voyage minimum. The calculations of speed vs. draft and trim surfaces are created according to hull resistance data generated by CFD, model tests, or real ship measurements, and these surfaces are used to calculate the OTWV. Ultimately, a trim and Main Engine (ME) power joint optimization method is developed based on the OTWV to make the total fuel consumption minimum for a voyage with a fixed length and travel time. A 307000 DWT VLCC is taken as an example to validate the practicality and effect of the two proposed optimization methods. The trim optimization example indicates that the OTWV could save up to 1.2% of the total fuel consumption compared to the Optimal Trim at Initial Draft (OTID). The trim and ME power joint optimization results show that the proposed method could steadily find the optimal trim and ME power combination, and the OTWV could save up to 1.0% fuel consumption compared to the OTID in this case.

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Seasonal effects on aboveground biomass estimation in mountainous deciduous forests using ZY-3 stereoscopic imagery - Wenjian Ni; Tianyu Yu; Yong Pang; Zhiyu Zhang; Yating He; Zengyuan Li; Guoqing Sun (Remote Sensing of Environment, 2023)

Study on pollution evolution law of coal and rock mixed dust in coal–oil shale fully mechanized mining face: a study case - Gang Zhou; Yu Ma; Ruixin Song; Yating Hu; Yongwei Liu; Bingyou Jiang; Biao Sun (Environmental Science and Pollution Research, 2023)

Deviations of satellite-measured sea surface salinity caused by environmental factors and their regional dependence - Yating Ouyang; Yuhong Zhang; Jianwei Chi; Qiwei Sun; Yan Du (Remote Sensing of Environment, 2023)

Pollution and occupational protection of diesel particulate matter in underground space - Yang Yang; Gang Zhou; Bingyou Jiang; Qi Wang; Yating Hu; Biao Sun (Environmental Science and Pollution Research, 2023)

Enhancement of the relationship between spring extreme precipitation over Southwest China and preceding winter sea surface temperature anomalies over the South Indian Ocean after the late 1980s - Yating Nan; Jianqi Sun; Mengqi Zhang; Haixu Hong; Yanbo Nie; Junpeng Yuan (International Journal of Climatology, 2022)
Spring extreme precipitation (SEP) significantly disturbs spring ploughing over Southwest China (SWC), bringing challenges for agricultural activities and production over the region. This study investigates the interannual relationship between SWC SEP and sea surface temperature (SST) in preceding winter, from a perspective of prediction. It is found that the dominate mode of SWC SEP interannual variability mainly reflects the variability over the eastern part. The variability of eastern SWC SEP has an enhanced connection with a dipole SST pattern over the South Indian Ocean in preceding winter after the late 1980s. Under the warmer SST background after the late 1980s, the South Indian Ocean dipole SST pattern can lead to significant convection activity over tropical central and western Indian Ocean. The tropical diabatic heating associated with enhanced convection can strengthen the western North Pacific anticyclone, which transports more water vapour to eastern SWC and induces stronger moisture convergence there, providing favourable moisture condition for the SEP occurrence. In addition, the dipole SST pattern can strengthen upward motion over eastern SWC through exiting a meridional circulation, providing a favourable dynamic condition for the SEP occurrence over there. In contrast, under the colder SST background before the late 1980s, the dipole SST pattern‐related convection and atmospheric circulation anomalies are weak over the Indo‐Pacific region. Therefore, the relationship of the dipole SST pattern with SEP over eastern SWC is weak before the late 1980s. The SST signals with one‐season leading could provide valuable source for seasonal prediction of eastern SWC SEP variability after the late 1980s.

MCPIP1 alleviated alcohol-induced immune dysfunction via the MAPK/ERK signaling pathway - Yanjie Shen; Kai Zhang; Rui Wang; Shuaichen Sun; Yating Yang; Yitan Yao; Huanzhong Liu; Zhenhua Ren (Psychopharmacology, 2022)

Numerical simulation investigation on optimal air volume for dilution dust-gas by forced ventilation in fully mechanized driving face - Gang Zhou; Yating Hu; Ruixin Song; Biao Sun; Yongwei Liu; Yang Yang (Environmental Science and Pollution Research, 2022)

Regional difference of sea surface salinity variations in the western tropical pacific - Yating Ouyang; Yuhong Zhang; Jianwei Chi; Qiwei Sun; Yan Du (Journal of Oceanography, 2021)
Regional difference of sea surface salinity (SSS) variations in the western tropical Pacific is investigated with Ocean Reanalysis System 5 datasets. Three robust zonal bands of SSS variations have been identified in the northwestern tropical Pacific (NWTP), the western equatorial tropical Pacific (WEqP), and the southwestern tropical Pacific (SWTP), respectively. SSS in the WEqP and the SWTP has a strong interannual variability that is related to ENSO. In the WEqP, SSS variations are mainly controlled by anomalous freshwater flux, while in the SWTP they are governed by both freshwater forcing and oceanic processes. In the NWTP, SSS variations present a low-frequency variability that is correlated with Interdecadal Pacific Oscillation (IPO), which is mostly dominated by the freshwater flux and strongly adjusted by the ocean advection and mixed layer changes. After removing interannual signals, the SSS in all three regions are highly related to IPO, indicating that IPO has a general influence on the western tropical Pacific.

The contrasting effects of thermodynamic and dynamic processes on East Asian summer monsoon precipitation during the Last Glacial Maximum: a data-model comparison - Yong Sun; Haibin Wu; Masa Kageyama; Gilles Ramstein; Laurent Z. X. Li; Ning Tan; Yating Lin; Bo Liu; Weipeng Zheng; Wenchao Zhang; Liwei Zou; Tianjun Zhou (Climate Dynamics, 2021)
The Last Glacial Maximum (LGM; 21 ka BP) was the most recent glacial period when the global ice sheet volume was at a maximum. Therefore, the LGM can be used to investigate atmospheric dynamics under a climate that differed significantly from the present. This study quantitatively compares pollen records of boreal summer (June–July–August) precipitation with the PMIP3 LGM simulations. The data-model comparison shows an overall agreement on a drier than pre-industrial East Asian summer monsoon (EASM) climate. Nevertheless, 17 out of 55 records show a regional precipitation increase that is also simulated over the additional land mass area due to sea level drop. The thermodynamic and dynamic responses are analyzed to explain a drier LGM EASM as a combination of these two antagonistic mechanisms. Relatively low atmospheric moisture content was the main thermodynamic control on the lower LGM (relative to pre-industrial levels) EASM precipitation amounts in both the reconstructions and the models. In contrast, two dynamic processes in relation to stationary eddy activity act to increase EASM precipitation regionally in records and simulations, respectively. Precipitation increase in records is explained by dynamic enhancement of the horizontal moisture transport, while dynamic enhancement of the vertical moisture transport leads to simulated precipitation increase over the specific region where landmass was exposed during LGM along continental coastlines of China due to significant drop in sea level (relative to pre-industrial levels). Overall, the opposing effects of thermodynamic and dynamic processes on precipitation during the LGM provide a means to reconcile the spatial heterogeneity of recorded precipitation changes in sign, although data-model comparison suggests that the simulated dynamic wetting mechanism is too weak relative to the thermodynamic drying mechanism over data-model disagreement regions.

Quantitative climatic reconstruction of the Last Glacial Maximum in China - Haibin Wu; Qin Li; Yanyan Yu; Aizhi Sun; Yating Lin; Wenqi Jiang; Yunli Luo (Science China Earth Sciences, 2019)

Microbial degradation of organophosphorus pesticides: novel degraders, kinetics, functional genes, and genotoxicity assessment - Bo Jiang; Nana Zhang; Yi Xing; Luning Lian; Yating Chen; Dayi Zhang; Guanghe Li; Guangdong Sun; Yizhi Song (Environmental Science and Pollution Research, 2019)

Dynamic Effects of Ioversol on the Permeability of the Blood-Brain Barrier and the Expression of ZO-1/Occludin in Rats - Heying Wang; Tao Li; Lili Zhao; Man Sun; Yating Jian; Jiao Liu; Yiheng Zhang; Ye Li; Meijuan Dang; Guilian Zhang (Journal of Molecular Neuroscience, 2019)

A new biflavonoid and a new triterpene from the leaves of Garcinia paucinervis and their biological activities - CuiCui Jia; Tong Han; Jun Xu; ShengGe Li; YaTing Sun; DaHong Li; ZhanLin Li; HuiMing Hua (Journal of Natural Medicines, 2017)

The effect of Fe-Mn minerals and seawater interface and enrichment mechanism of ore-forming elements of polymetallic crusts and nodules from the South China Sea - Yao Guan; Xiaoming Sun; Xiaodong Jiang; Rina Sa; Li Zhou; Yi Huang; Yating Liu; Xiaojie Li; Rongfei Lu; Chi Wang (Acta Oceanologica Sinica, 2017)

Three new xanthones from the leaves of Garcinia lancilimba - Yating Sun; Dahong Li; Cuicui Jia; Chunmei Xue; Jiao Bai; Zhanlin Li; Huiming Hua (Journal of Natural Medicines, 2016)

Effects of a conversion from grassland to cropland on the different soil organic carbon fractions in Inner Mongolia, China - Yuchun Qi; Yunshe Dong; Qin Peng; Shengsheng Xiao; Yating He; Xinchao Liu; Liangjie Sun; Junqiang Jia; Zhijie Yang (Journal of Geographical Sciences, 2012)

Effect of culture temperature on TNFR-Fc productivity in recombinant glutamine synthetase-chinese hamster ovary cells - Li Fan; Liang Zhao; Zhaoyang Ye; Yating Sun; Tianci Kou; Yan Zhou; Wen-Song Tan (Biotechnology Letters, 2010)